CARACTERISTICAS HIDROQUIMICAS Y COMPOSICION QUIMICA DE LOS SEDIMENTOS DE LA BAHIA DE NENGUANGE, CARIBE COLOMBIANO - Ramírez T., Gustavo (Boletín de investigaciones marinas y costeras, 2016)
Hydrochemical characteristics of the surface water and several chemical compounds of the sediment in Nenguange Bay were analized in 1982-1983. Seasonal variation of the hydrochemical parameters in three zones of the bay leads to consider two periods in the annual cycle. In the dry season (December to April) temperatures are lower (< 25°C) and salinities are higher (> 37.3 °/oo), which suggests a coastal upwelling phenomenon. During the rainy season, (May to November) the data show different conditions of temperature ( > 29°C) and salinity (<35°/oo), as a reflection of the arrival of continental freshwater; such process seems to make an equal or higher contribution than the upwelling to the inorganic nutrientes of the bay. The coastal lagoon in the southeast side is unstable and shows a wide range of temperature, salinity and dissolved oxigen. Finally, the distribution of organic materials in the sediments from southeast zone of the bay is analyzed.